Problematika Peran Guru Dalam Membentuk Profil Belajar Pancasila Pada Era Digital Kelas IV MI Miftahul Ulum Sidowungu Gresik - Lita Aditya K. N; Noviandani Kartika P.; Wachid Yuli Irfanto (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2022)
This study aims to see how the implementation of the Pancasila student profile program in the independent curriculum also wants to find out whether it has an impact on the formation of students' attitudes at school. This study found that the implementation of the Pancasila Student Profile application was not optimal because there were various obstacles that resulted in a lack of descriptions informed by educators, including limited time informed by educators, limited time for Teaching and Learning Activities, little subject matter, limited knowledge Technology that is tried by educators, student attention is very lacking in subjects and so on. There are also implications for the formation of attitudes or resilience of individual learners or students. The Pancasila Student Profile has the main goal of maintaining the nation's noble values ​​and morals, readiness to become a world citizen, realizing social justice, and achieving 21st Century competencies. The students referred to here are superior human resources who are lifelong students who have global competence and behave according to Pancasila values. The results of this study indicate that the implementation of Pancasila student profiles in schools is still not optimal and the implications for the formation of student attitudes are very strong. So that if the profile of Pancasila students is optimized in its implementation at school, a Pancasila student attitude will be formed.